Oxytetracycline hyper-production through targeted genome reduction of Streptomyces rimosus - Pšeničnik, Alen; Slemc, Lucija; Avbelj, Martina; Tome, Miha; Šala, Martin; Herron, Paul; Shmatkov, Maksym; Petek, Marko; Baebler, Špela; Mrak, Peter; Hranueli, Daslav; Starčević, Antonio; et al. (mSystems, 2024)
There is a critical need to develop novel antibiotics to combat antimicrobial resistance. Streptomyces species are very rich source of antibiotics, typically encoding 20–60 biosynthetic gene clusters (BGCs). However, under laboratory conditions, most are either silent or poorly expressed so that their products are only detectable at nanogram quantities, which hampers drug development efforts. To address this subject, we used comparative genome analysis of industrial Streptomyces rimosus strains producing high titers of a broad spectrum antibiotic oxytetracycline (OTC), developed during decades of industrial strain improvement. Interestingly, large-scale chromosomal deletions were observed. Based on this information, we carried out targeted genome deletions in the native strain S. rimosus ATCC 10970, and we show that a targeted deletion in the vicinity of the OTC BGC significantly induced expression of the OTC BGC, as well as some other silent BGCs, thus suggesting that this approach may be a useful way to identify new natural products.